Odpowiedź :
5^12*(9 - 5)*(2^3)^3
------------------------ = 4 5^12 należy wyłączyć przed nawias
2^9*5^12 i skrócić ułamek
7*7^12 7*7^12
---------- = --------------- = 7
(7^4)^3 7^12
------------------------ = 4 5^12 należy wyłączyć przed nawias
2^9*5^12 i skrócić ułamek
7*7^12 7*7^12
---------- = --------------- = 7
(7^4)^3 7^12
(9*5¹²-5¹³)*8³
------------------------=
2⁹ *(5⁴)³
5¹²(9-5)*8³
------------------------=
2⁹ *5¹²
5¹² się skraca
4*8³
----------=
2⁹
2² * (2³)³
----------=
2⁹
2² * 2⁹
----------= 4 2⁹ skraca się
2⁹
------------------------=
2⁹ *(5⁴)³
5¹²(9-5)*8³
------------------------=
2⁹ *5¹²
5¹² się skraca
4*8³
----------=
2⁹
2² * (2³)³
----------=
2⁹
2² * 2⁹
----------= 4 2⁹ skraca się
2⁹